Association of cumulative social risk with mortality and adverse cardiovascular disease outcomes - Sebhat Erqou; Justin B. Echouffo-Tcheugui; Kevin E. Kip; Aryan Aiyer; Steven E. Reis (BMC Cardiovascular Disorders, 2017)
Abstract Background Quantifying the cumulative effect of social risk factors on cardiovascular disease (CVD) risk can help to better understand the sources of disparities in health outcomes. Method and results Data from the Heart Strategies Concentrating on Risk Evaluation (HeartSCORE) study were used to create an index of cumulative social risk (CSR) and quantify its association with incident CVD and all-cause mortality. CSR was defined by assigning a score of 1 for the presence of each of 4 social factors: i) racial minority status (Black race), ii) single living status, iii) low income, and iv) low educational level. Hazard ratios (HRs) were computed using Cox-regression models, adjusted for CVD risk factors. Over a median follow-up period of 8.3 years, 127 incident events were observed. The incidence of the primary outcome for subgroups of participants with 0, 1, and ≥2 CSR scores was 5.31 (95% CI, 3.40–7.22), 10.32 (7.16–13.49) and 17.80 (12.94–22.67) per 1000 person-years, respectively. Individuals with CSR score of 1 had an adjusted HR of 1.85 (1.15–2.97) for incident primary outcomes, compared to those with score of 0. The corresponding HR for individuals with CSR score of 2 or more was 2.58 (1.60–4.17). Conclusion An accumulation of social risk factors independently increased the likelihood of CVD events and deaths in a cohort of White and Black individuals.